Psoriasis of the nails and scalp - Misciali, C... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1999)
About 50% of patients with psoriasis present involvement of the nails and/or the scalp. Psoriasis limited exclusively to these regions is not rare. Koebnerphenomenon can at least partially explain the localization of psoriasisin these areas, which are continuously exposed to traumas. Manual work and pedal biomechanics are responsible for repetitive micro traumas to the fingernails and the toenails, respectively, while brushing and combing cause traumas to the scalp. Although the histological findings of nail and scalp psoriasis are very similar to those of psoriasis of the glabrous skin, the clinical manifestations are substantially different, reflecting the particular anatomy and physiology of these regions.
Keywords: Alopecia; Nail diseases; Parakeratosis; Pathology; Psoriasis